Challenging History: Past Reconstruction in Colum McCann’s Songdogs - Andrzej Gabiński (Estudios Irlandeses, 2007)
The present paper analyses the way in which Colum McCann’s novel Songdogs (1995) constitutes an attempt at reconstructing and reconciling oneself with the past, a theme that a number of contemporary critics perceive as characteristic of the Irish literary experience. It will be argued that via the novel’s non-linear, fragmented narrative structure, on the one hand, and its frequent use of static images reminiscent of photography on the other, McCann engages the concept of memory and translates its founding functional principles into a personal literary technique. The task of recovering significance from distinct media – be it still images or the novel’s texture – will be construed as operating on two levels. The novel’s mixed plot lines constructed out of apparently unrelated clusters of images and the reader’s efforts at organising them into larger meaningful compositions will be understood as parallel to the protagonist’s attempts at forging all the stories embedded in Songdogs into a master narrative of his family’s history.